2012
DOI: 10.1007/s00256-012-1376-7
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral synchronous tibial periosteal osteosarcoma with familial incidence

Abstract: Multifocal or multicentric osteosarcoma (OS) has been described as tumor occurrence at two or more sites in a patient without visceral metastasis. These may be synchronous (more than one lesion at presentation) or metachronous (new tumor developing after the initial treatment). The incidence of multifocal OS has ranged from 1.5 to 5.4% in large series, with the synchronous type being rarer. Similarly, periosteal OS is another rare subtype of surface OS and constitutes less than 2% of all OS. An 11-year-old fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Genetic factors may be a novel approach for further research in periosteal osteosarcoma. Maheshwari et al found the TP53 gene (exon 8) mutation in two PO patients [3]. In our patient, genetic analysis of the tumour showed a TP53 (exon 8) p.R280K point mutation, and CCNE1 gene copy number variants (CNVs).…”
Section: Discussionsupporting
confidence: 46%
“…Genetic factors may be a novel approach for further research in periosteal osteosarcoma. Maheshwari et al found the TP53 gene (exon 8) mutation in two PO patients [3]. In our patient, genetic analysis of the tumour showed a TP53 (exon 8) p.R280K point mutation, and CCNE1 gene copy number variants (CNVs).…”
Section: Discussionsupporting
confidence: 46%
“…Skip metastasis usually emerges in the same bone, while those occurring in different bones are named transarticular skip metastasis. Synchronous multifocal lesions refer to more than one lesion at presentation without visceral metastasis[ 31 , 32 ]. Synchronous multifocal lesions have been reported in osteosarcoma, MFH, and chondrosarcoma[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is wide consensus regarding aggressive resection being used for PO (1,17,18). Tumors have been reported to spread further than could be imaged using CT or MRI, and in addition, an incomplete tumor resection is considered as the most important risk factor for an adverse outcome.…”
Section: Discussionmentioning
confidence: 99%